2021
DOI: 10.1051/shsconf/20219201030
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Equity Crowdfunding Projects: Are They A Driving Force to Revitalise Italy After Global Socio-Economic Consequences of The COVID-19?

Abstract: Research background: The outbreak of COVID-19 has disrupted and shaken all economic and financial sectors. In this scenario, crowdfunding has emerged as a new relevant financing mechanism alongside more traditional funding channels by attracting investors through an internet-based method of fundraising to support ventures. In recent years, many crowdfunding platforms, specialized in green projects rose, allowing start-ups to raise funds for their campaigns. The literature on the use of crowdfunding in the sust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In line with that, Ardiansyah (2019) stated that fintech such as equity crowdfunding really helps MSMEs in obtaining sources of capital funding to maintain and improve their business performance. Manganiello and Dragulanescu (2021) claimed that ECF services have a significant effect on improving performance, because there are other motivations such as refunds that affect investor decisions. This can help business actors who are in need of additional capital to develop their businesses and achieve optimal business performance.…”
Section: Relationship Between Variables and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with that, Ardiansyah (2019) stated that fintech such as equity crowdfunding really helps MSMEs in obtaining sources of capital funding to maintain and improve their business performance. Manganiello and Dragulanescu (2021) claimed that ECF services have a significant effect on improving performance, because there are other motivations such as refunds that affect investor decisions. This can help business actors who are in need of additional capital to develop their businesses and achieve optimal business performance.…”
Section: Relationship Between Variables and Hypotheses Developmentmentioning
confidence: 99%
“…Several researchers previously studied the application of equity crowdfunding services as a source of financing for MSME businesses and the effects of partnerships on MSME performance partially. Research conducted by Manganiello and Dragulanescu (2021) revealed that equity crowdfunding services have a significant effect on improving environmental performance, because there are other motivations for returning money that affect investors decisions. Ardiansyah (2019) said that fintech such as equity crowdfunding can help MSMEs in obtaining funding sources to maintain and improve business performance.…”
mentioning
confidence: 99%
“…Elmer et al, 2021). Moreover, donation-based crowdfunding platforms witnessed a surge in the number of COVID-19-related campaigns to support local communities, medical workers, small businesses, and personal medical and funeral expenses(Saleh et al, 2021) Manganiello and Dragulanescu (2021). highlighted the case of an Italian equity crowdfunding platform where investors are more willing to support projects with sustainable orientations after COVID-19.…”
mentioning
confidence: 99%